2018
DOI: 10.3390/bioengineering5020028
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Use of Stem Cells for Myocardial Infarction

Abstract: Myocardial infarction is a leading cause of morbidity and mortality worldwide. Although medical and surgical treatments can significantly improve patient outcomes, no treatment currently available is able to generate new contractile tissue or reverse ischemic myocardium. Driven by the recent/novel understanding that regenerative processes do exist in the myocardium—tissue previously thought not to possess regenerative properties—the use of stem cells has emerged as a promising therapeutic approach with high ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 108 publications
(157 reference statements)
1
46
0
5
Order By: Relevance
“…Therefore, stem cell therapy has emerged as a new treatment method. 67 However, despite the great development of this therapy, the delivery of targeted stem cells and the tracking or detection of their proliferation still need efforts to optimize. In order to overcome these shortcomings, new methods are needed to achieve high concentration cells in damaged tissues and to monitor their proliferation and survival.…”
Section: Nps Application In the Treatment Of Amimentioning
confidence: 99%
“…Therefore, stem cell therapy has emerged as a new treatment method. 67 However, despite the great development of this therapy, the delivery of targeted stem cells and the tracking or detection of their proliferation still need efforts to optimize. In order to overcome these shortcomings, new methods are needed to achieve high concentration cells in damaged tissues and to monitor their proliferation and survival.…”
Section: Nps Application In the Treatment Of Amimentioning
confidence: 99%
“…Traditional clinical approaches for myocardial infarction rely on surgical revascularization procedures, such as coronary stenting or coronary artery bypass grafts (CABG). Although the novel therapeutics using cells (especially stem cells) ( Gao et al, 2013 ; Madigan and Atoui, 2018 ; Terashvili and Bosnjak, 2019 ), genes ( Oggu et al, 2017 ), exosomes ( Davidson and Yellon, 2018 ), and growth factors ( Crafts et al, 2015 ; Reboucas et al, 2016 ) are emerging and have shown significant research outcomes, numerous challenges still exist in translating those technologies into clinical practice ( Egwim et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Стволовые/прогениторные клетки, рассматриваемые как альтернативный способ терапии сердечной недостаточности, способствуют регенерации поврежденного миокарда при инфаркте миокарда (ИМ) [15,19]. Показано, что аутологичные костномозговые мононуклеары при ишемии миокарда способствуют улучшению сократительной функции левого желудочка сердца, как следствие ангиогенеза в миокарде, опосредованного эндотелиальными прогениторными клетками (ЭПК) костного мозга [16,18].…”
Section: Introductionunclassified